2009
DOI: 10.1007/s00122-009-1122-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers for establishing distinctness in vegetatively propagated crops: a case study in grapevine

Abstract: Distinctness, uniformity and stability (DUS) testing of varieties is usually required to apply for Plant Breeders' Rights. This exam is currently carried out using morphological traits, where the establishment of distinctness through a minimum distance is the key issue. In this study, the possibility of using microsatellite markers for establishing the minimum distance in a vegetatively propagated crop (grapevine) has been evaluated. A collection of 991 accessions have been studied with nine microsatellite mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 28 publications
1
26
0
3
Order By: Relevance
“…These values indicate that the whole SNP set has a very high discriminating capacity for grapevine varieties, and is supported by the very low global probability of identity (PI): 1.4·10 -17 . This value is much smaller than that obtained with the 6 SSR markers approved as descriptors by the International Organisation of Vine and Wine (OIV) in the analysis of 57 unique Spanish genotypes (10 -7 [30]) and with 9 microsatellites in the analysis of 164 European cultivars (10 -9 [31]), or of 991 grapevine accessions (7·10 -12 , [23]). In contrast, the PI obtained for the 48 SNP set is larger than the value obtained with 18 microsatellites in 2,739 grapevine accessions (10 -22 , [21]), or with 34 microsatellites in 745 accessions (10 -27 [32]).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…These values indicate that the whole SNP set has a very high discriminating capacity for grapevine varieties, and is supported by the very low global probability of identity (PI): 1.4·10 -17 . This value is much smaller than that obtained with the 6 SSR markers approved as descriptors by the International Organisation of Vine and Wine (OIV) in the analysis of 57 unique Spanish genotypes (10 -7 [30]) and with 9 microsatellites in the analysis of 164 European cultivars (10 -9 [31]), or of 991 grapevine accessions (7·10 -12 , [23]). In contrast, the PI obtained for the 48 SNP set is larger than the value obtained with 18 microsatellites in 2,739 grapevine accessions (10 -22 , [21]), or with 34 microsatellites in 745 accessions (10 -27 [32]).…”
Section: Resultsmentioning
confidence: 78%
“…Currently, intra-laboratory genetic identification of grapevine varieties does not represent a major problem given the large number of microsatellite and SNP markers that have become available over the years [6,7,21-23]. However, it is very important to develop a system that is efficient, rapid and cheap for identifying the several thousand cultivars currently available in grapevine.…”
Section: Resultsmentioning
confidence: 99%
“…SSR genotype is usually the same in wild type and mutant. This study revealed the different SSR patterns between the original varieties and sports as in grape (Crespan, 2004;Ibáñez et al, 2009). Maybe some changes occurred in these three genotypes after a long cultivation, domestication, and intercrossing history.…”
Section: Discussionmentioning
confidence: 77%
“…"Character-specific molecular markers" are positively considered by UPOV's BMT to be used in DUS testing, provided that they can reliably estimate traditional characteristics (UPOV, 2013). Until now, the function of molecular markers evaluated for variety registration was unknown (Giancola et al, 2002;Rotondi et al, 2003;Bernet et al, 2003;Kwon et al, 2005;Gunjaca et al, 2008;Noli et al, 2008;Ibañez et al, 2009). Moreover, these markers were irrelevant to morphological traits that are currently used in DUS testing of new plant varieties.…”
Section: Discussionmentioning
confidence: 99%
“…Various molecular markers with unknown function or without association with morphological characteristics were used in DUS testing of crops (Giancola et al, 2002;Gunjaca et al, 2008;Noli et al, 2008), vegetables (Bernet et al, 2003;Kwon et al, 2005), and fruit trees (Rotondi et al, 2003;Ibañez et al, 2009). Lombard et al (2000), using amplified fragment length polymorphisms (AFLPs), could distinguish rapeseed cultivars according to growth type (winter vs. spring), country of origin, and breeding company of varieties.…”
Section: Introductionmentioning
confidence: 99%